The Role of Employee Welfare in Improving Work Productivity in Service Companies - Sabil Sabil; Lukman Hakim; Mohammad Amas Lahat; Rosento Rosento (West Science Interdisciplinary Studies, 2023)
This comprehensive bibliometric analysis explores the intricate relationship between employee welfare and work productivity in the context of service companies. Examining a diverse body of literature through systematic quantitative methods, the study identifies key themes, trends, and research gaps. The findings highlight the pivotal role of employee welfare, spanning healthcare benefits, workplace safety, and a supportive organizational culture, in shaping a positive work environment. The study underscores the direct impact of employee well-being on engagement, job satisfaction, and overall productivity. Practical implications encompass informed human resource practices, strategic interventions, and the optimization of work environments, offering actionable insights for practitioners and policymakers. Recognizing the strategic advantage in linking employee well-being to organizational success emerges as crucial for attracting and retaining top talent. Furthermore, the analysis points to less-explored research avenues, guiding scholars toward areas such as "work discipline," "business outcomes," and "profitability." In essence, this bibliometric study bridges academia and practice, advocating for a holistic and evidence-based approach to human resource management, positioning employee welfare as a strategic imperative for sustained success.